Quantitative analysis of high jump styles - Frosio, I.; Girlanda, M.; Botton, C.; Sibella, F.; Borghese, A. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The purpose of this study is to investigate the relationship between the kinematics and the dynamics in the elite high jumpers. The analysis was based on an accurate anthropometrical model of the body and on the kinematics data obtained through optical motion capture in an indoor training session. The measure of the angular momentum has given suggestions on how to improve the efficiency of the gesture. The analysis of the kinematics coordination and of the inter-trial variability suggest that athletes should focus more either on the kinematics or on the dynamics. From these data, the angular momentum and the kinematics variability do not appear to be correlated. KEY WORDS: high jump, 3D motion capture, kinematics, modelling.